2019
DOI: 10.1161/circoutcomes.119.005493
|View full text |Cite
|
Sign up to set email alerts
|

Michigan Stroke Transitions Trial

Abstract: Background: To test whether access to home-based social worker–led case management (SWCM) program or SWCM program combined with a website providing stroke-related information improves patient-reported outcomes in patients with stroke, relative to usual care. Methods and Results: The MISTT (Michigan Stroke Transitions Trial), an open (unblinded) 3-group parallel-design clinical trial, randomized 265 acute patients with stroke to 3 treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 42 publications
0
65
1
Order By: Relevance
“…The overall burden of stroke is considerable and continues to increase in the context of an ageing population (GBD, 2016Stroke Collaborators, 2019. Most stroke survivors are discharged to home, and the hospital-to-home transition poses many challenges for them and family caregivers to manage care at home whilst engaging in rehabilitation and recovery (Lindblom et al, 2020;Reeves et al, 2019). These challenges have become more prominent in the context of shortened hospital stays and early discharge by which stroke patients and their caregivers take charge of care activities and coordinate care services instead of health professionals in hospital (Camicia et al, 2016;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall burden of stroke is considerable and continues to increase in the context of an ageing population (GBD, 2016Stroke Collaborators, 2019. Most stroke survivors are discharged to home, and the hospital-to-home transition poses many challenges for them and family caregivers to manage care at home whilst engaging in rehabilitation and recovery (Lindblom et al, 2020;Reeves et al, 2019). These challenges have become more prominent in the context of shortened hospital stays and early discharge by which stroke patients and their caregivers take charge of care activities and coordinate care services instead of health professionals in hospital (Camicia et al, 2016;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most stroke survivors live with declined functioning such as poor balance, incontinence, swallowing difficulties, visual disturbances and psychological and cognitive disorders (Jokinen et al, 2015;Wainwright et al, 2017). Hospital readmissions are common after discharge and are associated with increased morbidity, mortality and risk of early institutionalisation (Abreu et al, 2020;Reeves et al, 2019). Contributing factors to readmissions include falls, urinary tract infection and recurrence of stroke (Abreu et al, 2020;Kilkenny et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] These patients, who are repeatedly transferred from hospitals to their homes often do not get high-quality information support; resulting Open access in a poor quality of continuing care, especially in medication information and discharge plan implementation. [17][18][19][20] Therefore, for this special vulnerable group, we need to ensure high-intensity information support in carrying out their transitional care. 21 22 This is cost-effective for the country, both in terms of economy and social benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived treatment control is a predictor of higher medication adherence in other conditions [19], this dimension should be addressed in specific educational programs providing information and support in behavior change particularly for persons who do not have access to rehabilitation services. In this way, several studies showed the effectiveness of community stroke educational groups [35,36]. Combining several media of information and educational support could improve survivors capability to use the information provided, as in nurse-led education programs [37], websites designed for this aim [36,38], case management [36], and peer-support groups [39].…”
Section: Discussionmentioning
confidence: 99%